Long-Term Walnut Oligopeptides Prevents Memory Loss in Aged SAMP8 Mice by Decreasing Oxidative Stress and Down-rRgulating the PI3K/Akt Signaling Pathway in Hippocampus. (29th May 2020) - Xu, Meihong; Du, Qian; Hao, Yuntao; Fan, Rui; Li, Yong
Abstract: Objectives: Walnut Oligopeptides (WOPs), the effective component of walnut, has been reported to have a neuron protective effect, but the preventive effect on Alzheimer's disease (AD) related memory loss and the underlying mechanisms have not been well determined. Methods: The senescence-accelerated mouse (SAM) is a useful model of AD-related memory impairment. In the present study, SAMP8 mice aged 4 months were chronically treated with ginsenoside (3 dose groups were given WOPs in diet for 6 months). The three groups were treated with WOPs 110, 220 and 440 mg/kg · bw per day, respectively. Placebo-treated aged mice and young ones (4 months old) were used as controls. In addition, SAMR1 mice were used as "normal aging" control. Results: The beneficial role of WOPs was manifested in the prevention of memory loss in aged SAMP8 mice. The optimal dose of WOPs is 220 or 440 mg/kg per day. WOPs as found to significantly improve the memory ability of AD rats and anti-oxidase level significantly increased in serum. WOPs also reduced the content of Aβ and p-tau and improved the expression of PI3K and p-Akt/Akt in the hippocampus. Conclusions: In conclusion, WOPs could improve the memory ability and reduce the content of Aβ and p-tau in SAMP8. The beneficial effects of WOPs were in part mediated by PI3K/Akt signaling pathway activation. Funding Sources: This research was funded by the Bioactive Peptide Innovation Platform in Jilin province.